Promotion of homology-directed DNA repair by polyamines - Lee, Chih-Ying (Nat Commun, 2019)
Polyamines, often elevated in cancer cells, have been shown to promote cell growth and proliferation. Whether polyamines regulate other cell functions remains unclear. Here, we explore whether and how polyamines affect genome integrity. When DNA double-strand break (DSB) is induced in hair follicles by ionizing radiation, reduction of cellular polyamines augments dystrophic changes with delayed regeneration. Mechanistically, polyamines facilitate homologous recombination-mediated DSB repair without affecting repair via non-homologous DNA end-joining and single-strand DNA annealing. Biochemical reconstitution and functional analyses demonstrate that polyamines enhance the DNA strand exchange activity of RAD51 recombinase. The effect of polyamines on RAD51 stems from their ability to enhance the capture of homologous duplex DNA and synaptic complex formation by the RAD51-ssDNA nucleoprotein filament. Our work demonstrates a novel function of polyamines in the maintenance of genome integrity via homology-directed DNA repair.